CdSe-sensitized mesoscopic TiO2 solar cells exhibiting >5% efficiency : redundancy of CdS buffer layer - Hossain, Md. Anower (2013)
Semiconductor-sensitized TiO2 solar cells employing CdSe as a light absorber demonstrate superior photovoltaic performance to the best-performing cascaded CdS/CdSe cells with practically identical optical density in the study. A careful comparison between CdSe and CdS/CdSe sensitized cells reveals that while CdS can greatly promote the subsequent growth of CdSe in the cascade electrodes and hence light harvesting, the presence of a CdS buffer layer impedes the injection of electrons from CdSe to TiO2 and accelerates charge recombination at the TiO2/sensitizer interface. As a result, better performance was achieved with CdSe-sensitized solar cells when light absorption is identical to that of CdS/CdSe cells, making the CdS buffer layer redundant. CdSe-sensitized TiO2 solar cells incorporating light scattering layers and an aqueous polysulfide electrolyte yielded an unprecedented power conversion efficiency of up to 5.21% under simulated AM 1.5, 100 mW cm−2 illumination.